2019
DOI: 10.1038/s41467-019-10766-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum FHR1 binding to necrotic-type cells activates monocytic inflammasome and marks necrotic sites in vasculopathies

Abstract: Persistent inflammation is a hallmark of many human diseases, including anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) and atherosclerosis. Here, we describe a dominant trigger of inflammation: human serum factor H-related protein FHR1. In vitro, this protein selectively binds to necrotic cells via its N-terminus; in addition, it binds near necrotic glomerular sites of AAV patients and necrotic areas in atherosclerotic plaques. FHR1, but not factor H, FHR2 or FHR3 strongly induces inflammasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 64 publications
1
81
0
Order By: Relevance
“…6C, lanes 7 and 9, respectively) were used. All mass and molar ratios of CFH to FHR1 used are in agreement with the majority of physiological ratios reported (36,(38)(39)(40)(41)(42). Independent of the concentrations used, cofactor activity for FI was not observed for FHR1 alone (Fig.…”
Section: A Gwas Reveals a Cluster Of Genetic Variants Within Cfhr Gensupporting
confidence: 84%
See 1 more Smart Citation
“…6C, lanes 7 and 9, respectively) were used. All mass and molar ratios of CFH to FHR1 used are in agreement with the majority of physiological ratios reported (36,(38)(39)(40)(41)(42). Independent of the concentrations used, cofactor activity for FI was not observed for FHR1 alone (Fig.…”
Section: A Gwas Reveals a Cluster Of Genetic Variants Within Cfhr Gensupporting
confidence: 84%
“…5G, and SI Appendix, Fig. S9B) (36). These data demonstrate that both FHR1 and FHR3 identify MDA-epitopes at sites of membrane damage, albeit with different affinities.…”
Section: A Gwas Reveals a Cluster Of Genetic Variants Within Cfhr Genmentioning
confidence: 65%
“…Similar to FHR-5, the extent of FHR-1 binding was increased when the cells became apoptotic or necrotic ( Figure 6 ). A recent study also found FHR-1 binding to necrotic HUVEC but not to live HUVEC ( 59 ). Binding of FHR-1 and FHR-5 to cells depends on available receptors and surface ligands; for example, previously we did demonstrate FHR-1 binding to viable neutrophils via the complement receptor CR3 ( 60 ).…”
Section: Discussionmentioning
confidence: 87%
“…Monocytes with CFHR3-CFHR1 deletion secreted higher level of IL-1β in response to LPS challenge (32). Necrotic cells bound to FHR-1 promotes the secretion of TNF-α, IL-1β, IL-18, and IL-6 by monocytes (33). These reports suggest multiple effects of CFHR1 deletion and highlight its complexity.…”
Section: Introductionmentioning
confidence: 85%